Analisis Pengaruh Dinamika Sosial Terhadap Metodologi Tafsir Persatuan Islam - Fajar Hamdani Akbar (Jurnal Iman dan Spiritualitas, 2021)
This study attempts to analyze the influence of the social dynamics surrounding the Islamic Union's mufassir on the methodology of his interpretation. The use of the method in this study focuses on qualitative methods, namely a research method that seeks to produce descriptive data in textual sentences or verbal expressions of a person and behavior that can be investigated. The overall data collection mechanism uses library research and interviews. This study indicates that the motives and social dynamics faced by the Islamic Union mufassir tend to influence the choice of the methodology of interpretation. The interpretation methodologies used by the Islamic Union exegetes in a manhāj khās (systematic presentation of interpretation) are relatively diverse. In terms of manhāj 'ām (method, source, and style), the Islamic Association commentator in interpreting the verse prefers the tahlīlī and maudhū'ī methods. The basis of the interpretation is bi al-matsūr, while the style is more focused on adab al-ijtimā'ī and akhlaqī. The choice of this method and style is nothing more than an effort by the Islamic Association commentator to bridge the principles of the teachings of the Qur'an as a guide for mankind.